Citizens and the state - Klingemann, Hans-Dieter; Fuchs, Dieter (Beliefs in government, 1995)
It is generally believed that the relationship between citizens and the state in West European democracies has undergone a fundamental change in the last decades. Many observers regard this change as a challenge to representative democracy. This book addresses the problem from the citizen's perspective. Singling out the ten fundamental components of the view that representative democracy is under threat, the book goes on to test them empirically by drawing on the extraordinary data set supplied by the Beliefs in Government research project.